Why Organizations Fail: Models and Cases - Garicano, Luis; Rayo, Luis (Journal of Economic Literature, 2016)
Organizations fail due to incentive problems (agents do not want to act in the organization's interests) and bounded rationality problems (agents do not have the necessary information to do so). This survey uses recent advances in organizational economics to illuminate organizational failures along these two dimensions. We combine reviews of the literature with simple models and case discussions. Specifically, we consider failures related to short-termism and the allocation of authority, both of which are instances of “multitasking problems”; communication failures in the presence of both soft and hard information due to incentive misalignments; resistance to change due to vested interests and rigid cultures; and failures related to the allocation of talent and miscommunication due to bounded rationality. We find that the organizational economics literature provides parsimonious explanations for a large range of economically significant failures. (JEL D21, D23, D82, D83, M10)